Understanding ageing : images, attitudes and proffessional practice - Biggs, Simon, 1955- (Open University Press, 1993)
Outward understanding. Inward understanding. Body, time and image. Self-perception and older age. Intergenerational communication. Power and opperession. Older people and practitioners...